Closed-loop multibody kinematic optimization coupled with double calibration improves scapular kinematic estimates in asymptomatic population. (20th September 2021) - Blache, Y.; Degot, M.; Duprey, S.; Begon, M.; Rogowski, I.
Abstract: Non-invasive methods still need to better estimate scapular kinematics because of soft tissue artifact issue. This study aimed to develop and assess new procedures to estimate scapular kinematics by combining closed kinematic chain optimization and double calibration. Sixteen healthy volunteers performed static postures mimicking analytical and daily living movements. Scapulo-thoracic angles were computed either with a scapula locator ( Ref ), or with a closed-loop multibody kinematic optimization ( Ell ) or with double calibration involving linear ( DClin ), exponential ( DCexp ) or logarithmic ( DClog ) correction. Double calibration corrections enforced scapulo-thoracic angles to be the same than those measured with Ref at the end of the movement performed. DClin and DClog significantly (p < 0.01) reduced scapulo-thoracic misorientation for at least the second third of the movement with averaged improvement ranging from 9° to 32°. Moreover, for arm elevation in the sagittal plane, internal rotations and mimicking hair combing, the beneficial effect of DClin and DClog propagates up to half of the movement. To conclude, when a kinematic chain is required, coupling double calibration (using either linear or logarithmic correction), to a closed-loop multibody kinematic optimization is an efficient and fast method in regard with improvement in scapular kinematic estimates in healthy population.